Placing Brazil's grasslands and savannas on the map of science and conservation - Overbeck, Gerhard Ernst; Vélez-Martin, Eduardo; Menezes, Luciana da Silva; Anand, Madhur; Baeza, Santiago; Carlucci, Marcos B.; Dechoum, Michele S.; Durigan, Giselda; Fidelis, Alessandra; Guido, Anaclara; Moro, Marcelo Freire; Munhoz, Cássia Beatriz Rodrigues; et al. (Perspectives in plant ecology, evolution and systematics, 2022)
In Brazil, the country with the highest plant species richness in the world, biodiverse savannas and grasslands – i.e., grassy ecosystems, which occupy 27% of the country – have historically been neglected in conservation and scientific treatments. Reasons for this neglect include misconceptions about the characteristics and dynamics of these ecosystems, as well as inconsistent or regionally restricted terminology that impeded a more adequate communication about Brazil's savannas and grasslands, both within the country and internationally. Toward improved communication and recognition of Brazil’s diversity of ecosystems, we present the key drivers that control the main types of grassy ecosystems across Brazil (including in regions of the country where forests dominate). In doing so, we synthesize the main features of each grassy ecosystem in terms of physiognomy and ecological dynamics (e.g., relationships with herbivores and fire). We propose a terminology both for major grassland regions and for regionally relevant vegetation physiognomies. We also discuss terms associated with human land management and restoration of grassy ecosystems. Finally, we suggest key research needs to advance our understanding of the ecology and conservation values of Brazil’s grassy ecosystems. We expect that a common and shared terminology and understanding, as proposed here, will stimulate more integrative research that will be fundamental to developing improved conservation and restoration strategies. [Display omitted] •27% of Brazil’s natural vegetation are grasslands and savannas.•Brazil’s grassy ecosystems remain undervalued in conservation: 46% have been converted to other uses.•Eleven major regions of grassy ecosystems can be identified across Brazil.•Disturbances (e.g., fire, grazing) are key determinants of Brazil’s grassy ecosystems.•Efforts are needed to map grassy ecosystems and develop conservation strategies.